High-speed imaging of second-harmonic generation in mos2 bilayer under femtosecond laser ablation - Kim, Young Chul; Yoo, Hoseong; Nguyen, Van Tu; Lee, Soonil; Park, Ji Yong; Ahn, Yeong Hwan (Nanomaterials, 2021)
We report an in situ characterization of transition-metal dichalcogenide (TMD) monolayers and twisted bilayers using a high-speed second-harmonic generation (SHG) imaging technique. High-frequency laser modulation and galvano scanning in the SHG imaging enabled a rapid identification of the crystallinity in the TMD, including the orientation and homogeneity with a speed of 1 frame/s. For a twisted bilayer MoS2, we studied the SHG peak intensity and angles as a function of the twist angle under a strong interlayer coupling. In addition, rapid SHG imaging can be used to visualize laser-induced ablation of monolayer and bilayer MoS2 in situ under illumination by a strong femtosecond laser. Importantly, we observed a characteristic threshold behavior; the ablation process occurred for a very short time duration once the preheating condition was reached. We investigated the laser thinning of the bilayer MoS2 with different twist angles. When the twist angle was 0°, the SHG decreased by approximately one-fourth of the initial intensity when one layer was removed. Conversely, when the twist angle was approximately 60° (the SHG intensity was suppressed), the SHG increased abruptly close to that of the nearby monolayer when one layer was removed. Precise layer-by-layer control was possible because of the unique threshold behavior of the laser-induced ablation.
Keywords: Laser ablation; Second-harmonic generation; Transition-metal dichalcogenides; Twisted bilayer